2017
DOI: 10.3892/ol.2017.5857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and anticancer activities of transition metal complexes with a nicotinohydrazone ligand

Abstract: Abstract. The reaction of divalent transition metal salts and (E)-N'-(1-(pyridin-2-yl)ethylidene)nicotinohydrazide (penh) led to the formation of [Mn(penh) 2 ] (complex 1), [Co(penh) 2 ] (complex 2), [Cu(penh) 2 ] (complex 3) and [Cd (penh) 2 ] (complex 4) complexes. The four complexes were characterized using elemental analyses, infrared spectra and single-crystal X-ray diffraction analyses. Subsequently, the complexes were used for in vitro cell level experiments to determine potential antitumor effects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Shen et al [41] reported the synthesis and characterization of divalent transition metal complexes e.g., Co(II), Cu(II), Cd(II) and Mn(II) with nicotinohydrazide ligand. The complex also used for in vitro cell experiment to test the antitumour effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al [41] reported the synthesis and characterization of divalent transition metal complexes e.g., Co(II), Cu(II), Cd(II) and Mn(II) with nicotinohydrazide ligand. The complex also used for in vitro cell experiment to test the antitumour effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the uncomplexed ligand show cytotoxic effect than the metal complexes. Metal complexes can effectively decrease the proliferation rate of different type of cancerous cell line like human gastric cancer cells, human esophageal cancer cell line (ECA109) in a dose dependent manner [41].…”
Section: Introductionmentioning
confidence: 99%
“…The results that obtained the metal complexes have significant ability to inhibit cancer cell proliferation, and that the effect is higher than the free ligand (NaH 2 PH), which proposed that the chelated transition metal in the complex plays essential role in enhancing the complex activities. [ 55 ] The Hg (II) complex displayed the highest anticancer activities against liver cancer (HePG‐2) and breast cancer (MCF‐7) cell lines. It means that the chemical structure of the examined compounds play an important role in the biological properties and produce a new anticancer drug.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that improving the activities of transition metals depends critically on their coordination. 63 This activity is based on their ability to bind DNA, which causes them to damage or modify their structure, decreasing their ability to perform their role. 25 According of the results, the complex has the potential to be used as a promising anticancer drug in vivo to halt the DNA replication in the cancer cells and to stop the growth of the tumor.…”
Section: Anticancer Activitymentioning
confidence: 99%